Renewable energy consumption and Inclusive Growth: Evidence from 20 African countries - Asiedu Ampomah Benjamin (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
In Africa, the need for energy is growing. When it comes to renewable energy resources in Africa zone, it is unequivocally needed. Many African countries are experiencing development therefore they are shifting to the use of renewable energy. In that view, this study aims to discover the potential impact of renewable energy consumption on inclusive growth in 20 African countries for a period covering 1997 To 2015. To tackle this estimation technique namely Pesaran's (2007) [1] CD test, Pesaran's (2015) [2] LM test and Breusch and Pagan's (1980) [3] LM test, slope homogeneity test, Average Mean Group (AMG), Common Correlated Effects Mean Group (CCEMG) and pairwise granger were employed. Concentration on inclusive growth contributes greatly to the economy size and ensures employment opportunity creation for the society in a different segment, the result of the study indicates that renewable energy consumption significantly impacted inclusive growth in n the selected Africa Countries. Consequently, if countries like Africa prosper in switching to renewable energy, unbelievable gains could be captured in terms of inclusive growth.